A Study on the Performance of Feature Extraction Methods According to the Size of N-Gram - Man Kwon, Young; Gu Son, Min; Keun Chung, Dong; jae Lim, Myung (International Journal of Engineering and Technology, 2018)
In this paper, we studied the performance of feature extraction methods according to the size of N-gram for malware detection. The feature is extracted by three methods, using Opcode Only, both Opcode and API and API Only from PE file. We measure the performance of them indirectly with measuring the AUC score and accuracy of classifier. We did experiments with the different N size by using several classifiers such as DT, SVM, KNN and BNB classifiers. As a result, we got the conclusion as followings. If we use N-gram technique, we recommend Opcode Only method through our experiments. Also, the instance-based classifier KNN and DT among the model based classifier have good performance than SVM and BNB.Â Â